IMPLEMENTASI PENDEKATAN SAINTIFIK DALAM MATERI OPERASI ARITMATIKA PADA CALON GURU SD - Yus Mochamad Cholily; Beti Istanti Suwandayani (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2019)
This study had a purpose to explore and describe the implementation of mathematics learning in the arithmetic operations teaching material of the pre-service elementary school teachers. This study employed a qualitative approach with a descriptive type. The subjects of this study were the students from batch 2019 of the Teacher Professional Education (PPG) at Muhammadiyah Malang University. The data in this study were obtained through document review, observation and interviews. The study was conducted during three meetings of the learning activities in class. The instruments in this study were observation instruments and interview instruments. Data analysis technique was conducted by using data reduction, data presentation, and conclusions. The results showed that the implementation of mathematics learning was carried out with a learning design, pre-service elementary school teachers understood the language of mathematics incorrectly. Pre-service teacher could not describe the difference between the minuses and negatives. This misunderstanding had an impact on the misleading learning process for the students. Moreover, some factors dealt with the use of the teaching media for the learning process was also not in a sufficient amount.